Pengembangan Model Adopsi Teknologi pada UMKM Manufaktur Kota Kediri setelah Era Pandemi COVID-19 - Elisa Bidari; Iwan Inrawan Wiratmadja (Program Studi Teknik Industri, Fakultas Teknologi Industri, Institut Teknologi Bandung, 2023)
Over the past decade, the development of industrial technology has become a concern among industry and academia. This attention has become even greater with the onset of the COVID-19 pandemic. To be able to rise up and avoid the losses caused by the upcoming pandemic in the future, reducing the physical human touch in industry is what is needed now. Kediri City is one of the cities in Indonesia affected by the COVID-19 pandemic. The Gross Regional Domestic Product (GRDP) of Kediri City has decreased significantly because many Micro, Small and Medium Enterprises (MSMEs) have reduced the number of employees or experienced bankruptcy. To increase the GRDP of Kediri City, MSMEs can adopt industrial technology 4.0, but there is a lack of understanding of the factors that influence the adoption of digital technology. This study aims to determine what factors influence the adoption of industrial technology 4.0 by manufacturing MSMEs in Kediri City in the post-pandemic era using the Technology, Organizational, Environmental (TOE) model. 76 manufacturing MSMEs in Kediri City were obtained as respondents, the data were then processed using the PLS-SEM method. The results showed that observability, market transparency, top management support and championship, satisfaction with existing systems, market uncertainty, and government support significantly influenced the adoption of Industry 4.0 technology by manufacturing SMEs in Kediri City in the post-pandemic era. Meanwhile, percieved trend does not have any influence on the adoption of Industry 4.0 technology by manufacturing MSMEs in Kediri City in the post-pandemic era.